Peran Komite Etik dan Hukum Rumah Sakit Dalam Peningkatan Mutu Pelayanan, Keselamatan Pasien, dan Penyelesaian Sengketa Medik Di Rumah Sakit Syarif Hidayatullah Tahun 2023 - Mahesa Paranadipa Maikel; Yanuar Jak; Fresley Hutapea (Majalah Kedokteran Indonesia, 2024)
Introduction: The Hospital Ethics and Law Committee (HELC) holds the primary responsibility of ensuring adherence to ethical and legal regulations within the hospital. However, due to the absence of specific provisions regarding the HELC, its role has often not been fully optimized. This study aims to evaluate the role of the HELC in enhancing the quality of services, ensuring patient safety, and resolving medical disputes at Syarif Hidayatullah Hospital, Jakarta. Methods: This cross-sectional study combines quantitative and qualitative methods, involving employees of Syarif Hidayatullah Hospital as respondents. Data collection was conducted through interviews from January to February 2024. The data were analyzed using univariate and bivariate methods, followed by multivariate variance analysis. Results: A total of 53.1% of respondents assessed the role of the HELC as well-executed. An effectively executed HELC role is correlated with increased patient safety, enhanced service quality, and effective resolution of medical disputes (all p less than 0.001). Multivariate variance analysis revealed that the HELC's role has the most significant impact on the improvement of hospital service quality (adjusted R-squared = 0.885). Conclusion: The role of the HELC is associated with improvement of patient safety, service quality, and the resolution of medical disputes in Syarif Hidayatullah Hospital. Hospital management needs to empower the HELC and enhance coordination with other committees and units within the hospital.